Observational Checklist for assessing the quality of contact visits during family foster care. - García-Martín, Miguel Ángel; Bernedo-Muñoz, Isabel María; Salas-Martínez, María Dolores; González-Pasarín, Lucía (Wiley, 2023)
This study explores whether the frequency and diversity of behaviours observed during contact visits may be used as indicators of visit quality. We observed 20 contact visits and quantified the frequency and diversity of behaviours for both parent and child, classified as positive or negative with respect to the child's well-being. Quality of visits was classified based on a list of parent and child behaviours and two indicators (diversity and frequency), to create two observational checklists and calculate an overall quality index. This observational tool will enable identification of areas where birth parents or their child require additional support.
Keywords: Acogimiento familiar; Trabajo social; Niños - Protección, asistencia, etc.; Contact visits; Foster care; Observational checklist; Visit quality